Site Response Analysis Gedung Asrama LPMP Sumbar dari Input Motion Conditional Mean Spectrum (CMS) Menggunakan Software NERA - Merley Misriani (Jurnal Fondasi, 2019)
In the design of earthquake resistant building structures, site response analysis is performed for the proposed dormitory building of LPMP Sumbar. In this research, earthquake wave propagation analysis from bedrock to surface layer (Site Response Analysis/ SRA) was conducted. SRA is based on probabilistic seismic hazard analysis (PSHA) previously conducted and refers to the uniform hazard spectra for 10% probabilisty of exceedence in 50 years (475 years return period) or 2% probabilisty of exceedence in 50 years (2475 years return period). The prediction of the structure response is determined by selecting the ground motion that matches several spectral targets and the ground motion is then used as input in dynamic analysis. The required data are soil stratification and shear wave velocity parameters obtained from empirical correlation to drilling result data and N-SPT test. Ground motion synthetic bedrock used for earthquake wave propagation is obtained from previous research that adopted the Conditional Mean Spectrum (CMS)statistical approach so that the ground motion produced on the surface matches the prediction of actual structural response problem. SRA is based on the theory of single-dimensional wave propagation in time domain using Non-linear Earthquake Response Analysis/NERA program. The results of this analysis are shown in the form of historical time acceleration graph, peak base acceleration (PBA), amplification factor and response spectra on the surface for the return period of 475 years and 2475 years. These data are used as inputs for the determination of earthquake load on buildings in dynamic structure analysis.